Variations in N2 fluxes in some hydrosequences in Malaysia - Padmanabhan, Eswaran (2011)
The major factors controlling N2O emissions include N application rate, climate and soil C content. Emissions patterns of N2O and NO from rice lands show that there is spatial variation in the amount of N2O and NO being emitted from rice lands. Considering the complexities involved in determining the fluxes of N2 or the various compounds, the current study focuses mainly on variations in N2 contents in a hydrosequence. Studies in forested areas show that both N2O flux and N2O concentrations were high in the wettest period and that nitrification or denitrification became increasingly dominant depending on moisture contents in pore spaces. Studies in a hydrosequence involving six pedons showed that the organic matter content also is inversely proportional to the drainage status. This inadvertently affects the N2 content as evidenced by reducing C/N ratios with improving drainage. This study shows that N2 flux is predominantly a function of local hydrology in alluvial soils in Peninsula Malaysia. Other co-determinant factors such as organic matter contents, microbial activities, C/N ratios, soil texture, just to name a few, play an important role as well. However, in order to maximize the utilization of these fragile resources in an environmentally safe manner, it is important that more studies be undertaken to evaluate the role of soil moisture in diverse landscape units at the micro- and meso-scales. It is therefore recommended that these paddy fields be managed through a redefined resource management domain concept. It is recommended that the RMD be defined based on several land and pedon characteristics that are endemic to the locality. This includes complexities in micro-topography, variations in parent material, hydrological characteristics, and critical soil properties.